Mucinous variant of invasive micropapillary carcinoma of breast: report of two cases and literature review - Yuan, Jing-Ping (Int J Clin Exp Pathol, 2017)
Invasive micropapillary carcinoma (IMPC) is a rare type of malignant tumor of breast with a poor prognosis. There is controversy in the identification of mucinous variant of IMPC with mucinous carcinoma. In the past, it always be diagnosed as micropapillary variant of mucinous carcinoma, but in this study, the author has a different opinion. Here, we report two cases diagnosed as mucinous variant of IMPC. Histological morphologies were similar in the two cases. In difference from mucinous carcinoma, mucinous variant of the IMPC is characterized by micropapillary structure of the tumor cells, higher nuclear atypia, more frequent HER2/Neu overexpression, high proliferation index of Ki-67, increased lymph node metastasis, and poor prognosis. A distinct feature of the 2 cases was that the tumor cells were present as micropapillary or tubular-solid clusters floating in the extracellular mucin pools and most of the floating tumor cells were surrounded by the hyaline lacunae, which can clearly be appreciated even in the background of mucin. Both patients were managed by the standard chemotherapy and radiotherapy combined with simple mastectomy. Up to the time of preparation of this report, both patients have survived for over 4 years. It is important to differentiate a mucinous variants of IMPC from a pure mucinous carcinoma due to their significantly different prognosis and, thereafter, different choices of patient management.